PENGARUH KEMAMPUAN KERJA KOMITMEN ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI - Suziana Wirmayanis (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
The purpose of this research is to explain workability, organizational commitment and motivation on employee performance. The purpose is also to describe workability, organizational commitment and work motivation. Sample is consisting of 94 employees that chosen with random stratified sampling. Research result shows that the workability, organizational commitment and work motivation simultaneously effect employee performance positively and significantly, with coefficient determination is 56.1%. Partially, workability, organizational commitment and motivation effect employee performance. Furthermore, according to statistical result, workability has more dominant effect. Research recommendation is to implement technical training to increase both employee ability and organizational commitment. Key Words. Workability, Organizational Comittment, Job Satsifaction, Performance, City Jambi Health Affairs